Effect of nanofillers on the spreading behavior of biopolymer materials on urea surface - Samsudin, Y.N. (Trans Tech Publications Ltd, 2014)
This paper presented new approach where a new modified biopolymer reinforced with bentonite nanoclay is developed and used as the coating material for controlled-release fertilizer. Good wettability properties between coating material and urea surface is necessary to provide uniformity during the coating process of controlled release fertilizer. Seven different blending ratio of modified biopolymer solutions are prepared and evaluated for their wettability properties. The wettability properties measured include the surface tension, contact angle and maximum spreading diameter. Optical Contact Angle device comes with a Charged-Coupled Device (CCD) camera was used to capture every single image of the droplet impact behavior. From the analysis, it is proven that with addition of 2 nanoclay filler reinforced into modified biopolymer with blending ratio of 50/15/2.5/7.5 has the best wettability properties and provides better spreading behavior. Â© 2014 Trans Tech Publications, Switzerland.